FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEDAGANG DALAM MENGGUNAKAN PRODUK SIMPAN PINJAM KHUSUS PEREMPUAN PADA UNIT PENGELOLA KEGIATAN (UPK) SYARIAH MANDIRI KECAMATAN SELAKAU - Febrianty, Nurul Aulia; Ananda, Iva Ashari (Cross-Border Journal of Business Management, 2026)
Women’s savings and loan product are a financing product from a sharia institution that has the aim of improving the economic situation of the community. Currently, there are many financial institutions such as bank and non-bank that help provide comprehensive support for the problems of people whose economy is middle to lower, such as traders. This research aims to determine what factors influence traders’ descisions in using SPP products and the SPP financing scheme at the UPK sharia independent sub-district Selakau. This research, including qualitative field research, data obtained by using observation, techniquest, interviews and documentation techniques. This research uses 3 kinds of data analysis techniques namely data reduction, data presentation, and drawing conclusions. The result of this research indicate that the factors that influence traders’ descisions to use these financing product are internal factors such as personal and psychological, as well external factors such as social from the surrounding environment, the ease of the system for custumer to use, provit sharing between institutions and customers, requirements for financing, as well as services provided by the independent sharia activity management unit institutions in the Selakau Sub-district.